Reorienting Educational Efforts for Sustainable Development : Experiences from South Asia - Gorana, Rajeswari Namagiri; Kanaujia, Preeti Rawat (Springer Netherlands : Imprint: Springer, 2017)
Education in South Asia has a renewed agenda which can enable societies to leapfrog development that is sustainable such that the individual is prepared for his/her involvement, responsibility and commitment to local and global discussions of our common future. This book on South Asia will focus on initiatives under the Education for Sustainable Development (ESD) umbrella and discuss the challenges, opportunities, issues and strategies in the countries of the region. It presents these initiatives of Environmental Education/ESD vis-à-vis the administrative, economic, social, cultural and ecological realities of each country at various levels of policy, planning, implementation and evaluation. The discussions in this book extend beyond formal education systems like schools, higher education, pre-service and in-service teacher preparation to community education and education initiatives conceptualized with the goal of sustainability. All initiatives will demonstrate how each country in its own pace contributing to move ESD from the periphery to the core of education initiatives.
Keywords: Social sciences.; Science education.; Sustainable development.; Human geography.; elektronické knihy; electronic books